Gap analysis of environmental licensing on oil palm plantations in eastern part of South Sumatra Province. Issue 4 (March 2021) - Komarudin, N A; Hariyadi, H; June, T
Abstract: The purpose of this study is to examine the gap analysis of environmental licensing both environmental permits, business licenses, and certification of oil palm plantations and their implementation in the field. This research is conducted in the eastern part of South Sumatra Province, focusing on six private companies in the field of oil palm plantations. Although the area has environmental management policies and regulations, many environmental problems still occur. This is indicated because there is a gap between the development of environmental policies related to licensing and their implementation in the field. The study is carried out using gap analysis method which is a common and simple technique in the evaluation of public policies. The results showed a gap value of less than 0.5 which indicates that the companies have implemented and complied in conducting business activities that refer to applicable environmental policies with the fulfilment of location permits and business licenses. It also signified that all companies have fulfilled the environmental permit component properly. However, there is a gap in terms of ownership of environmental certification. While almost all companies have already acquired ISPO (Indonesia Sustainable Palm Oil) certification, the government needs to provide assistance to companies to increase the company's readiness to complete certification.